A three-dimensional culture model of lipopolysaccharide-activated microglia - Haw, Tatt Yhew (2015)
In vitro studies utilising conventional two dimensional (2D) culture systems have been used regularly in countless research, although this approach has its own drawbacks. Cells loses their multi-layered histological organisation and interact only on one plane with a flat plastic surface. Furthermore, the competency of 2D culture has also become increasingly questionable when tackling complex 3D biological problems, such as response of the central nervous system (CNS) to injury or infection. Microglia is a type of macrophage that is found in the brain and acts as the main line of defence in the CNS by evoking inflammatory responses. With an interest in modelling the mechanical state of microglia embedded in CNS parenchyma, this study explored the use of type I collagen as a matrix for growth of microglial cells in a three dimensional (3D) manner. For this, BV2 microglia or primary mouse microglia cell suspensions were prepared with type I collagen and cast into culture plates. Keen to also determine whether microglia cultured in 3D were capable of shifting to an activated phenotype, cultures were treated with 1 μg/ml lipopolysaccharide (LPS) or costimulated with LPS and IFN-γ (for primary microglia). Concurrently, conventional 2D culture (monolayer and collagen coated-monolayer) were set-up for comparison. BV2 microglia cultured in 3D had a doubling time of 39.90  2.86 hours. It was also determined by the lactate dehydrogenase (LDH) assay that LPS was not cytotoxic to BV2 microglia. The expression of NO was determined using the Griess Assay. At 48 hours, the expression of NO for unstimulated BV2 microglia (resting state) in 3D was 2.33  0.56 μM. Upon LPS stimulation, the expression of NO by BV2 microglia in 3D significantly increased to 24.47  2.14 μM. Using RT-qPCR, the expression of inflammatory cytokine mRNA (IL-6, IL-10, IL-1β, IL-12β, MCP-1 and TNF-α) of poststimulated BV2 microglia in 3D culture were significantly upregulated. Additionally, a bead array was used to measure the level of cytokine protein expression (IL-6, IL-10,MCP-1, IFN-γ, TNF, and IL-12p70) by post-stimulated BV2 microglia. Expression of IL-10, IFN-γ and IL-12p70 were negligible. At 48 hours after LPS stimulation, only the protein levels of IL-6, TNF-α and MCP-1 of BV2 microglia significantly increased from 0.7 ± 0.8 pg/ml, 8.1 ± 3.1 pg/ml and 284.0 ± 73.5 pg/ml to 1999.0 ± 685.2 pg/ml, 1744.0 ± 911.6 pg/ml and 5403.0 ± 517.6 pg/ml (*p<0.5, **p<0.1; Mann Whitney Test) respectively. Primary microglia was obtained from brains of C57BL/6 mice. The viability of primary microglia in 3D was determined using DAPI/PI staining method. Primary microglia showed low PI staining (viable) after 72 hours of LPS and IFN-γ co-stimulation in 3D culture. The expression of NO by primary microglia cultured in 3D was in 3D 0.95  1.01 μM to 39.37  9.53 μM after a 72 hour co-stimulation. Using flow cytometry, CD40 expression of primary microglia cultured in 3D was determined. Percentage of CD40 expression increased from 59.0% and 39.3% to 85.7% and 90.9% after a 72 hour costimulation. In summary, microglia cultured in 3D undergo a robust activation response when stimulated with LPS/LPS with IFN-γ. Importantly, the 3D culture is able to model this activation response with minimum cell death, and the availability of both culture supernatant and cells for analysis can be done with relative ease. This model could provide a platform for other research to be conducted on the pathophysiology of neuroinflammatory processes.